IMPACT OF MICROPLASTICS CONTAMINATED FOOD AND BEVERAGES ON REPRODUCTIVE AND MENTAL HEALTH - Titilayo, Lala Opeyemi; Funmilayo, Adisa Ayomide; Motunrayo, Adelowo Joy; Eniola, Oladapo Jesutomi; Adeola, Oyekanmi Bolape; Gbenga, Lala Olusegun; Olanike, Afolabi Opeyemi; Adenike, Ajayeoba Titilayo; Elizabeth, Morakinyo Adetoun; Kolawole, Oladipo Elijah; Obukohwo, Oyowvi Mega; Adenike, Oyedepo Temitope (Folia Medica Indonesiana, 2025)
Microplastics, defined as plastic particles smaller than 5 mm, have emerged as a global environmental pollutant resulting from widespread plastic waste. Increasing concerns have been raised regarding their potential contamination of food and beverages, which may pose health risks to humans. This review aimed to evaluate current literature focusing on potential reproductive and mental health risks associated with the consumption of microplastic-contaminated food and beverages. A comprehensive literature search was conducted using multiple databases and Boolean operators to identify peer-reviewed English-language articles published within the past thirteen years. The review included studies that addressed microplastics in food and beverages, their health impacts particularly on reproductive and mental health and the techniques used for their detection and quantification. Studies not addressing these specific topics, non-English publications, and those published before the year 2000 were excluded. Evidence suggests that microplastics can enter the food chain through various routes, including ingestion by marine organisms, contamination during food processing, and leaching from plastic packaging. Consequently, microplastics have been detected in a wide range of food products, such as seafood, table salt, honey, and bottled water. Exposure to microplastics has been associated with endocrine disruption, alterations in gut microbiota, and neurobehavioral effects, potentially contributing to anxiety and depression through mechanisms involving oxidative stress, apoptosis, and inflammatory responses. Furthermore, microplastics may act as vectors for harmful additives and chemical contaminants, posing long-term health risks. Although current levels of exposure are generally low, the potential for cumulative effects underscores the need for further research to better understand associated risks and to develop effective mitigation strategies. As a precautionary measure, reducing the intake of processed and packaged foods in favor of fresh alternatives may help minimize microplastic exposure.